Amalan 5S dalam persekitaran rumah kediaman menurut perspektif Islam / Zahari Mahad Musa - Mahad Musa, Zahari (Universiti Teknologi MARA, Pulau Pinang, 2014)
The correlation between the 5S practices and homes is very significant. 5S is a system of quality management in the workplace housekeeping that originates in Japan. It is an acronym for the 5 key words with the initial letter ‘S’ in the Japanese language comprising Seiri, Seiton, Seiso, Seiketsu and Shitsuke. Meanwhile, a home is considered a fundamental part of environment and closely related to the quality of life. It is not only seen as a physical space, but it has become the cradle of social interaction and tranquility of community building. In Islam, the dwellings are substantial parts contributing to certain standard of quality and happiness in this life. This paper aims to discuss the practice of 5S and how it is related to the dwelling’s environment according to the Islamic view. The significance of the study is to assess the 5S practices in the dwelling’s environment. In addition, this research aims at ensuring that Islamic practices have also emphasized such approach despite having the 5S concept branding taking place in Japan. This is a qualitative study, whereby data collectionis done through library research. The discussion will be based on analysis of data inductively involving Islamic texts of the Quran and Sunnah. This description reveals that Islam prescribes a holistic guide about the dwellings. Recommendation of 5S practices in the dwelling’s environment is not alienated but in line with the daily fiqh itself. Additionally, this article can prove the need for a practical 5S practices at the dwellings apart from the usual discussion on the practice merely focusing on organizational management and workplace culture.